2020
DOI: 10.2174/1871520620666200619165910
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Silver and Zero-Valent Iron Nanoparticles by Feijoa: Biosynthesis, Characterization, Cytotoxic, Antibacterial and Antioxidant Activities

Abstract: Background: and Purpose: Green nanotechnology is an interesting method for the synthesis of functional nanoparticles. Because of their wide application, they have set up great attention in recent years. Objective: The present research examines the green synthesis of Ag and zero-valent iron nanoparticles (AgNPs, ZVINPs) by Feijoa sellowiana fruit extract. In this synthesis, no stabilizers or surfactants were applied. Methods: Eco-friendly synthesis of Iron and biogenic synthesis of Ag nanoparticles were ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The effect of incubation periods: Figure 2a clearly demonstrates that the absorbance of the mixture increased as the contact time increased from 30 min to 240 min, due to the evolution of the reduction in silver ions and the increase in the number of silver nanoparticles [54]. The UV-Vis spectra exhibited strong SPR absorbance after 240 min due to the stabilization of nanoparticles because of the stabilization agent present in the plant extract [55]. Then, the rate of reaction of the lemon zest mediated silver nanoparticles is 4 h, which is faster compared with the biosynthesis of AgNPs using Citrus tangerina, Citrus sinensis, and Citrus limon peel extracts [56].…”
Section: Optimization Of Different Experimental Factors In Biosynthes...mentioning
confidence: 99%
“…The effect of incubation periods: Figure 2a clearly demonstrates that the absorbance of the mixture increased as the contact time increased from 30 min to 240 min, due to the evolution of the reduction in silver ions and the increase in the number of silver nanoparticles [54]. The UV-Vis spectra exhibited strong SPR absorbance after 240 min due to the stabilization of nanoparticles because of the stabilization agent present in the plant extract [55]. Then, the rate of reaction of the lemon zest mediated silver nanoparticles is 4 h, which is faster compared with the biosynthesis of AgNPs using Citrus tangerina, Citrus sinensis, and Citrus limon peel extracts [56].…”
Section: Optimization Of Different Experimental Factors In Biosynthes...mentioning
confidence: 99%
“…Conventional HPLC was used using a C18 column to isolate phenolic acids. The extract contained 5 phenolic compounds such as catechins, gallic acid, caffeic acid, routine and p-coumaric acid (188.5, 18.5, 2.3, 8.15 and 4.7 g/ g, respectively;Hashemi et al, 2020).…”
Section: Hplc Separation Of Phenol Derivativesmentioning
confidence: 99%
“…AgNPs have been widely researched for their antibacterial properties against bacteria such as P. aeruginosa , P. vulgaris , E. coli , S. aureus , etc. [ 29 ]. A recent investigation by Verma et al reported the inverse cytotoxicity and enhanced antibacterial activity of the green-synthesized AgNPs [ 30 ].…”
Section: Applications Of Agnpsmentioning
confidence: 99%